Teaching Video and Workshop Exercises: "Putting the Patient First: Engineering Patient-Oriented Clinic Handoffs (EPOCH)" - Amber Pincavage; Wei Wei Lee; Shana Ratner; Megan Prochaska; Andrew Davis; Mark Saathoff; Vineet Arora (Association of American Medical Colleges, 2014)
Abstract Clinic handoffs occur when residents graduate and patients are transitioned to another primary care physician. Numerous patients are at risk for poor outcomes and face many barriers to effective care during clinic handoffs(1-5). Patients are lost to follow-up, have missed test results, miss screening opportunities and may require care in the emergency room or hospital as a consequence of the transition(3,4). Patients experience barriers in doctor-patient relationships, clinic logistics, care transition processes and patient safety preventing effective handoffs(5). There have been strategies demonstrated to improve patient outcomes during clinic handoffs but they have not focused on patient-centered care(6-8). Thus techniques to improve patient-centered care and educate residents regarding patient-centered care during clinic handoffs are needed. This video and activities will help residency programs improve patient-centered care during clinic handoffs. It will also assist residency programs meet ACGME handoff training requirements as well as milestones in the areas of professionalism, system-based practice and interpersonal and communication skills. Specifically the video and activities will help train residents in the following milestones: effective use of verbal and nonverbal skills to create rapport with patients, use of communication skills to build a therapeutic relationship, effective communication with other caregivers in order to maintain continuity during transitions of care, role model and teach effective communication with next caregivers during transitions of care and utilize patient-centered educational strategies. The audit tool will help programs monitor safety of their clinic handoffs. The process map will help programs begin quality improvement efforts and create their own process map. This video and video checklist has been presented at a workshop at 1 national conference and 2 resident didactic sessions at 2 different institutions. It has also been posted on Vimeo and viewed over 25 times. Evaluations of these tools at our institution demonstrated that 90% (N=21) of residents agreed that this video helped highlight the barriers patients face during clinic handoffs. 90% of residents agreed the workshop would be helpful in carrying out their year-end clinic handoff. 95% of residents agreed it is important to receive training in year-end clinic handoffs. 90% agreed the workshop was engaging. 86% learned new knowledge from the workshop. When this video and video checklist was used with residents at another local institution, 100% (N=14) agreed the video helped highlight the barriers patients face during clinic handoffs. 100% of residents agreed the workshop would be helpful in carrying out their year-end clinic handoff. 100% of residents agreed it is important to receive training in year-end clinic handoffs and 100% agreed the workshop was engaging. 93% learned new knowledge from the workshop. When this tool was used with medical educators at a national conference, 93% (N=27) of participants agreed the video and video checklist effectively highlighted the challenges patients face during clinic handoffs. 92% of participants agreed the video checklist is a useful teaching tool. 92% intended to use the tool for resident education and 39% for attending education.